Atypical ductal hyperplasia of the breast: clonal proliferation with loss of heterozygosity on chromosomes 16q and 17p. Issue 7 (July 1995) - Lakhani, S R; Collins, N; Stratton, M R; Sloane, J P
Abstract : AIMS--To determine if allelic loss on chromosomes 16q and 17p, commonly encountered in in situ and invasive ductal carcinomas, is present in atypical ductal hyperplasia (ADH); to determine whether ADH is a neoplastic (clonal) or hyperplastic (polyclonal) proliferation. METHODS--Fourteen cases of ADH were examined for allele loss at loci on chromosome 16q and 17p using a microdissection technique, polymorphic DNA markers and the polymerase chain reaction (PCR). RESULTS--Loss of heterozygosity (LOH) was detected in five of nine informative cases on chromosome 16q at the microsatellite D16S413 and two of eight informative cases on chromosome 17p at D17S796. CONCLUSIONS--The incidence of LOH at these loci is similar to that previously observed in ductal carcinoma in situ and in invasive ductal carcinoma. Because of the nature of the technique used, our findings also demonstrate that ADH is a monoclonal, and hence, neoplastic proliferation rather than a hyperplastic (polyclonal) condition as its name suggests. There is thus a case for including ADH, as presently defined, within the spectrum of ductal carcinoma in situ.